Effects of water salinity and organomineral fertilization on leaf composition and production in Passiflora edulis - José T. A. Souza; Járisson C. Nunes; Lourival F. Cavalcante; Juliete A. da S. Nunes; Walter E. Pereira; José L. de O. Freire (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT An experiment was undertaken in Remígio County, Paraíba State, Brazil, from July 2013 to May 2014, in order to evaluate the effects of saline water irrigation, bovine biofertilizer, and potassium type on soil salinity, leaf macronutrient composition, and production of yellow passion fruit cv. BRS Gigante Amarelo. Treatments were distributed in randomized blocks, arranged in a 2 × 2 × 2 factorial design, with reference to electrical conductivity of the water (0.35 and 4.00 dS m-1), soil with and without bovine biofertilizer, and application of potassium chloride as a conventional treatment (KCl) and in an organic polymer-coated form, supplied monthly. Bovine biofertilizer was diluted in non-saline water (proportion, 50%) and applied via water at a volume of 6 L plant-1 one day before transplanting, and then every 90 days. The combination of saline water with bovine biofertilizer raised soil salinity to a similar proportion when comparing saline water and conventional potassium chloride with saline water and polymer-coated potassium chloride. The increase in water saline concentrations associated with both types of potassium chloride and with bovine biofertilizer elevated soil salinity from non-saline to saline. On starting to flower, plants of cv. BRS Gigante Amarelo were deficient in macronutrients other than nitrogen and potassium, but nonetheless produced fruits of an adequate mass for the consumer market.